Bringing together the World Health Organization's QualityRights initiative and the World Psychiatric Association's programme on implementing alternatives to coercion in mental healthcare: a common goal for action - Neeraj Gill; Natalie Drew; Maria Rodrigues; Hassan Muhsen; Guadalupe Morales Cano; Martha Savage; Soumitra Pathare; John Allan; Silvana Galderisi; Afzal Javed; Helen Herrman; Michelle Funk (BJPsych Open, 2024)
Background Stakeholders worldwide increasingly acknowledge the need to address coercive practices in mental healthcare. Options have been described and evaluated in several countries, as noted recently in major policy documents from the World Health Organization (WHO) and World Psychiatric Association (WPA). The WHO's QualityRights initiative promotes human rights and quality of care for persons with mental health conditions and psychosocial disabilities. A position statement from the WPA calls for implementation of alternatives to coercion in mental healthcare.